Analyzing Secondary Trademark Liability from the Perspective of Economic Strategy in US and Iranian Law - Najafi, Hamed (Frontiers in Law, 2025)
In US law, trademark infringement can occur in two ways: direct and indirect. In the latter case, a person, without committing an act that constitutes trademark infringement, performs a behavior that, depending on the case, results in the realization of participatory (and motivational) or vicarious liability. Considering the state of technological innovation in America, the identification of such an institution seems justified. In the Iranian legal system, indirect liability for trademark infringement is not foreseen and various instances of this type of infringement are subject to general civil liability regulations, which is logical considering the state of technological innovation in Iran. The purpose of the present study, using a desc riptive-analytical method, is to examine the liability for indirect trademark infringement from the perspective of its effects in the field of technology. The US situation in terms of technology justifies the recognition and application of such a liability, considering its elements.However, considering the state of technological innovation in Iran and considering all the circumstances, including international regulations, Iran’s political-economic situation in the international arena, etc., the failure to recognize the entity of indirect liability resulting from trademark infringement and reliance on general civil liability provisions in this context is justified and recommended.